Do Individuals Put Effort into Lying? Evidence from a Compliance Experiment - Nadja Dwenger; Tim Lohse (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study whether individuals in a face-to-face situation can successfully exert some lying effort to delude others. We exploit data from a laboratory experiment in which participants were asked to assess videotaped statements as being rather truthful or untruthful. The statements are face-to-face tax declarations. The video clips feature each subject twice making the same declaration. But one time the subject is reporting truthfully, the other time willingly untruthfully. This allows us to investigate within-subject differences in trustworthiness. We find that a subject is perceived as more trustworthy if she deceives than if she reports truthfully. It is particularly individuals with dishonest appearance who manage to increase their perceived trustworthiness by up to 15 percent. This is evidence of individuals successfully exerting lying effort.
Keywords: C91; H31; K42; H26; 330; lying effort; face-to-face communication; perceived trustworthiness; lie detection; compliance